Attitude, Subjective Norms, and The Adoption of Green Transportation Modes among Generation Z's Willingness to Travel to Kuala Lumpur - Ahmad, Siti Yuliandi; Ibrahim, Siti Hajar; Hama, Susan (International Islamic University Malaysia, 2025)
12| Journal of Contemporary Tourism andHospitality Research(JoCTH) Vol. 1, No. 1, September 2025ARTICLEAttitude, Subjective Norms, and The Adoption of Green Transportation Modes among Generation Z's Willingness to Travel to Kuala LumpurSiti Hajar Ibrahim1, Siti Yuliandi Ahmad2*, Susan Hama31,2Department of Tourism, Kulliyyah of Sustainable Tourism and Contemporary Languages, International Islamic University Malaysia,3Faculty of Management Sciences, Yala Rajabhat University, Thailand 1ibrahimhajar90@gmail.com2sitiyuliandi@iium.edu.my3susan.h@yru.ac.th*Corresponding author: sitiyuliandi@iium.edu.myABSTRACTAs climate change and environmental sustainability gain increasing global attention, the transportation sector, particularly in urban areas, is identified as a significant contributor to greenhouse gas emissions. Adoption of public transportation by tourists remains low, and current strategies often fail to meet tourists' needs and preferences, leading to suboptimal sustainable travel behaviours. This study investigates the adoption of green transportation modes among Generation Z tourists travelling to Kuala Lumpur, focusing on urban public transportation services, including buses, Light Rail Transit (LRT), Mass Rapid Transit (MRT), monorail, and commuter trains. Using the Theory of Planned Behaviour (TPB) as a theoretical framework, this research investigates the attitudes, subjective norms, and public transport adoption among Generation Z. A quantitative research method was employed, with data collected via self-administered questionnaires and analysed using IBM SPSS version 29. By understanding the behavioural drivers of green transportation adoption, this research contributes to developing strategies that enhance the attractiveness and efficiency of public transportation, ultimately reducing the environmental impact of tourism in Kuala Lumpur.